Pomen vključujoče družbe pri urejanju in nadzoru lobiranja - Kečanović, Bećir (Podjetje in delo, 2014)
The article addresses lobbying as a democratic achievement, allowing individual interests to compete for various forms of co-existence. In reference to the role of inclusive society, it establishes the need to curb the excessive power of political elites and lobbies by way of an increased role of the civil sector and non-profit lobbying service.
Keywords: democracy; demokracija; interesne skupine; lobiranje